Education On Providing Balanced Nutrition Towards the Level of Knowledge Of Mothers Of Stunting Toddlers - ria setia sari; Nur Haliza (Institut Citra Internasional, 2025)
Providing balanced nutrition for stunted toddlers. Mothers' knowledge about balanced nutrition is very much needed. Obtaining data from 116 stunted toddlers in February 2024, the health center has implemented a series of government programs. It has decreased from before but is still trying to reduce the number of stunting in the Rajeg Health Center area, and there is still a lack of knowledge of mothers about handling balanced nutrition. The purpose of this study was to determine whether or not there was an effect of balanced nutrition education on the level of knowledge of mothers of stunted toddlers. The research design used a quantitative research type with the Pre-Experimental Designs method using the One group pretest posttest design, and statistical analysis using the Wilcoxon test. Sampling technique: Using a non-probability sampling technique with a purposive sampling method, the number of samples was 54 respondents calculated using the Slovin formula. The results in this study were obtained in the Pre-test level of mother's knowledge with good knowledge 6 (11.1%), sufficient knowledge 11 (20.4%), and poor knowledge 37 (68.5%). While the post-test good knowledge 47 (87.0%), sufficient knowledge and 7 (13.0%) poor knowledge. Conclusion: there is a significant influence between balanced nutrition education and the level of knowledge of mothers of stunted toddlers.